ANALYSIS OF THE IMPACT OF RURAL DEVELOPMENT PROJECTS ON LOCAL COMMUNITIES - Marioara ILEA; Rezhen HARUN; Diana E. DUMITRAS; Felix H. ARION; Iulia C. MURESAN; Gabriela O. CHICIUDEAN; Hemin Abubakir NEIMA; Camelia F. OROIAN; Dan (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Considering the huge economic and social disparities between urban and rural areas of Romania, it is important to investigate the local community perception on the perceived impact of the rural development strategies, provided that local strategies should be developed based on citizens’ needs. The study represents a first step towards a more complex research to evaluate the degree of satisfaction and wellbeing of the rural communities from Cluj County, following the implementation of the rural development programs. The research was conducted on the basis of primary data obtained from citizens of Cuzdrioara, a commune from Cluj County which represents a particular case, as its position allows the direct connection to national roads. The data were analyzed using descriptive statistics and inferential statistics. The Chi-square test and Fisher's exact test were performed for comparisons of proportions, while Mann-Whitney test and Kruskal Wallis test were used for the comparisons of scale scores between respondents. Through the objectives of the Local Development Strategy, Cuzdrioara commune aims to improve the way of life of the inhabitants by achieving the objectives proposed in the strategy. Many projects have been completed, being positively assessed by the citizens. The public administration fulfilled the objectives established in the Local Development Strategy.